The Dynamics of Job Creation and Job Destruction: Is Sub-Saharan Africa Different? - Admasu Shiferaw; Arjun Bedi (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2010)
This paper analyzes the creation, destruction and reallocation of jobs to better understand the micro-dynamics of aggregate employment change in African manufacturing. The nature and magnitude of gross job flows are examined using a unique panel data of Ethiopian manufacturing establishments over the period 1996-2007. We also assess the relative importance of firm demographics, industry effects and business cycles for job flows. The rates and patterns of job creation and destruction in our sample are comparable to the findings from developed and emerging economies suggesting that African firms adjust their labor force in a manner broadly similar to firms elsewhere and that African labor markets are not uniquely restrictive to undermine job reallocation across firms. We also find, like in many other countries, that job reallocation is relatively higher in industries dominated by small and young establishments. Unlike in other regions, however, job reallocation in our sample is pro-cyclical and its cross-industry variation holds very little similarity with that of developed and emerging economies. Small firms in Africa create jobs mainly at the point of entry to a market with limited contribution to manufacturing employment through post-entry expansion.
Keywords: J20; J23; J49; 330; Job Creation; Job Destruction; Job Reallocation; Firm Dynamics; Sub-Saharan Africa; Ethiopia